2021
DOI: 10.1002/acm2.13294
|View full text |Cite
|
Sign up to set email alerts
|

Survey of patient‐specific quality assurance practice for IMRT and VMAT

Abstract: A first-time survey across 15 cancer centers in Ontario, Canada, on the current practice of patient-specific quality assurance (PSQA) for intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) delivery was conducted. The objectives were to assess the current state of PSQA practice, identify areas for potential improvement, and facilitate the continued improvement in standardization, consistency, efficacy, and efficiency of PSQA regionally. The survey asked 40 questions related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Patient-specific QA of treatment plans has been recommended for all IMRT or VMAT plans. Practically, patient-specific QA can be implemented for all plans or sampled for selected plans ( 37 , 38 ). For the sampling method, the selection criteria were either totally random or based on plenty of selection criteria, such as machine availability, plan complexity, economic factors, physicist time or preference, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific QA of treatment plans has been recommended for all IMRT or VMAT plans. Practically, patient-specific QA can be implemented for all plans or sampled for selected plans ( 37 , 38 ). For the sampling method, the selection criteria were either totally random or based on plenty of selection criteria, such as machine availability, plan complexity, economic factors, physicist time or preference, etc.…”
Section: Discussionmentioning
confidence: 99%
“…For the sampling method, the selection criteria were either totally random or based on plenty of selection criteria, such as machine availability, plan complexity, economic factors, physicist time or preference, etc. ( 37 ). So far, there is no uniform selection criterion or explicit guidelines for radiation therapy centers to screen patients for patient-specific QA ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…For our ultimate goal of PSQA failure prediction, we consider the same data in the classification context by thresholding the regression labels and converting them into binary classification labels. We defined the action threshold level in the gamma analysis to be at 95 % as is common in clinical practice 39,40,41 and obtained binary classification labels (pass or fail) based on this threshold. We reserved 65% of the samples for the training set, 15% for the validation set and 20% for the test set.…”
Section: Methodsmentioning
confidence: 99%
“…This re search was ac tu ated by changes in in terna tional rec om men da tions re gard ing tol er ance lev els [7]. Be sides this, the re cent stud ies [8,9] have shown that com mon tol er ance cri te ria used is still 3 % dose dif fer ence and 3 mm dis tance-to-agree ment. Thus, the first part of our re search in ves ti gates how changes in tol er ance in flu ence gamma pass ing rates.…”
Section: Introductionmentioning
confidence: 99%